Geocomputational Method to Determine the Effect of Serpentinized Ultramafic Rocks on Laterite Nickel Distribusion - Rohaya Langkoke; Adi Tonggiroh; Meinarni Thamrin; Umar Al Amir (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Administratively, the study area is located in Wolo District, Kolaka Regency, Southeast Sulawesi Province. This research aims to assess the relationship between the serpentinization process and the grades and distribution of laterite nickel. The methods employed include data collection through drilling, which involves logging procedures and laboratory analyses such as petrographic and geochemical analyses (X-Ray Fluorescence). The geocomputational method, Inverse Distance Weighting (IDW), is subsequently applied to determine the distribution of laterite nickel. Observations indicate that the bedrock in the study area consists of ultramafic rock types, including Lherzolite, Olivine Websterite, and Serpentinite. Some of these rocks have undergone serpentinization, while others have not. The serpentinization levels in the study area are classified into three categories: weak serpentinization (≤15%), moderate serpentinization (35%-50%), and strong serpentinization (55%-75%). Nickel grades in strongly serpentinized rocks are 0.22%, in moderately serpentinized rocks 0.50%, in weakly serpentinized rocks 0.32%, and in rocks that have not undergone serpentinization 0.30%.